Activity fingerprinting of AMR β-lactamase towards a fast and accurate diagnosis - Song, Chenchen; Sun, Xuan; Wang, Yao; Bülow, Leif; Mecklenburg, Michael; Wu, Changxin; Meng, Qinglai; Xie, Bin (Frontiers in Cellular and Infection Microbiology, 2023)
Antibiotic resistance has become a serious threat to global public health and economic development. Rapid and accurate identification of a patient status for antimicrobial resistance (AMR) are urgently needed in clinical diagnosis. Here we describe the development of an assay method for activity fingerprinting of AMR βlactamases using panels of 7 β-lactam antibiotics in 35 min. New Deli Metallo βlactamase-1 (NDM-1) and penicillinase were demonstrated as two different classes of β-lactamases. The panel consisted of three classes of antibiotics, including: penicillins (penicillin G, piperacillin), cephalosporins (cefepime, ceftriaxone, cefazolin) and carbapenems (meropenem and imipenem). The assay employed a scheme combines the catalytic reaction of AMR β-lactamases on antibiotic substrates with a flow-injected thermometric biosensor that allows the direct detection of the heat generated from the enzymatic catalysis, and eliminates the need for custom substrates and multiple detection schemes. In order to differentiate classes of β-lactamases, characterization of the enzyme activity under different catalytic condition, such as, buffer composition, ion strength and pH were investigated. This assay could provide a tool for fast diagnosis of patient AMR status which makes possible for the future accurate treatment with selected antibiotics.